2020
DOI: 10.1186/s13584-020-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved meals service and reduced food waste and costs in medical institutions resulting from employment of a food service dietitian – a case study

Abstract: Background: A recurring problem in medical institutions is patients not always receiving food meeting their nutritional and medical needs. A proposed contributing factor is non-inclusion of dietitians in food service staff. Recently, positions for food service dietitians in hospitals were created. For the newly defined role of "Food Service Dietitian", comprehensive training courses were developed (70 dietitians participated). Objective: To examine the impact of the addition of the role of a "Food Service Diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…Their demand for food and beverage services to be controlled by a dietitian were emphasized by university students and staff for "healthy nutrition". These findings were in agreement with those of Yona et al (25), who did a comprehensive study in Israel and documented significant nutritional care improvements and cost savings after recruiting food service dietitians in hospital kitchens. Employing dietitians not only resulted in menus to be analyzed in detail per portion, but also waste was reduced and the institutional budget was positively affected (25).…”
Section: Results Of the Quantitative Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Their demand for food and beverage services to be controlled by a dietitian were emphasized by university students and staff for "healthy nutrition". These findings were in agreement with those of Yona et al (25), who did a comprehensive study in Israel and documented significant nutritional care improvements and cost savings after recruiting food service dietitians in hospital kitchens. Employing dietitians not only resulted in menus to be analyzed in detail per portion, but also waste was reduced and the institutional budget was positively affected (25).…”
Section: Results Of the Quantitative Analysissupporting
confidence: 92%
“…These findings were in agreement with those of Yona et al (25), who did a comprehensive study in Israel and documented significant nutritional care improvements and cost savings after recruiting food service dietitians in hospital kitchens. Employing dietitians not only resulted in menus to be analyzed in detail per portion, but also waste was reduced and the institutional budget was positively affected (25). Since dietitians are trained professionally in providing Saturated fatty acid (g) Thiamine (B (22).…”
Section: Results Of the Quantitative Analysissupporting
confidence: 92%
“…This finding is consistent with a study conducted in a Malawi Burn unit; Grundziak et al, reported that all patients received the same foods daily, no matter the age or severity of burn [ 50 ]. The shortfalls observed for the quality of food provided by the hospital could be attributed to the lack of standard guidelines for menu standardization or nutritional content of food [ 51 , 52 , 53 ]. This demonstrates the opportunity for improving hospital food service, types and amount of food; the need for trained nutrition professionals, and most importantly, the political will to modify and improve hospital policy that will allow for these changes.…”
Section: Discussionmentioning
confidence: 99%
“…can impair implementation of the nutrition program. The consequence is patients not receiving the optimal food for their needs, according to the medical and nutrition guidelines issued in the department, even if the correct nutritional instructions were recorded [ 35 ]. Food safety is a critical factor in the preparation and serving of food to hospitalized patients, who are more likely than the general population to be susceptible to foodborne illness, due to their decreased health status [ 7 , 34 ].…”
Section: Approaches For Establishing Food Allergy Safety In Food Service Systemsmentioning
confidence: 99%
“…Generally, strategies that were previously demonstrated to improve meal tray accuracy in hospitals include a standardized menu formatting and spoken menu systems [ 38 ]. According to the Nutrition Division at the Ministry of Health in Israel, the continuity of care between hospital departments and hospital food services, as reflected in the serving of food that is appropriate to patients’ medical needs, is incomplete and even nonexistent in some hospital departments [ 35 ].…”
Section: Approaches For Establishing Food Allergy Safety In Food Service Systemsmentioning
confidence: 99%